Investigation on diseases of jute seed crop and possibility of seed production in West Bengal - S. SATPATHY, S.K. SARKAR* and (Indian Phytopathology, 2016)
Field experiment was conducted for disease-free quality jute seed production during 2009-2012 by altering the sowing dates and fungicide scheduling. Among seven dates of sowing, mid-August sown crop resulted in least seed infection (1.7%) by Macrophomina phaseolina and seed discolouration by various seed fungi. Other quality parameters like germination (88.2-91.50%) and seedling vigour also remain above the seed recommended standard (80%). Seed yield (13.2 q/ha) and yield attributes are also higher in mid-August sown crop than other dates of sowing. Foliar spraying of carbendazim 50WP @ 0.2% at pod setting or pod maturation stage resulted in least seed infection (2.3%) and seed discolouration which reflected on higher seed yield (11 q/ha) and yield attributes. The qualities of seeds are also improved due to foliar application of fungicide, carbendazim.